2022
DOI: 10.46827/ejel.v7i1.4176
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Perceived Collective Efficacy Beliefs and Interpersonal Emotion Regulation to Turkish Efl Teachers’ Job Stress

Abstract: The goal of this study was to explore the relationship between perceived job stress and a specific set of predictor variables among the selected university preparatory school EFL (English as a Foreign Language) teachers in Turkey. To comprehensively analyze the issue of perceived job stress, interpersonal emotion regulation, and teacher collective efficacy used as variables. The sample consisted of 48 EFL teachers in various Turkish university preparatory schools. It was hypothesized that high levels of teache… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
0
0
Order By: Relevance
“…Previous research studies showed that RSE increases as RTE increases in accordance with the SCCT theory (Lent et al, 1994). The environmental effect can stimulate students to develop RSE (Bieschke, et al, 1996;Eke andHayward, 2012, Gaoat et al, 2023;Gelso, et al, 2013;Khan & Scott, 1997;Livinƫi et al, 2021;Suna & Kemer, 2022), whereby RSE resulted in learning engagement and RE (Eginli & Dikilitas, 2022;Hall, 2010;Heng et al, 2020;Jorgenen & Ducan, 2015;Salgueira et al, 2012;Pachler et al, 2019;Wu et al, 2020). RTE serves RI, a tendency for students to conduct research after graduation, including conducting research to develop the field, conducting research for career advancement, and conducting social research (Burke & Prieto, 2019;Livinƫi et al, 2021;Snelgrove & James, 2010).…”
Section: The Conceptual Model Developmentmentioning
confidence: 78%
See 1 more Smart Citation
“…Previous research studies showed that RSE increases as RTE increases in accordance with the SCCT theory (Lent et al, 1994). The environmental effect can stimulate students to develop RSE (Bieschke, et al, 1996;Eke andHayward, 2012, Gaoat et al, 2023;Gelso, et al, 2013;Khan & Scott, 1997;Livinƫi et al, 2021;Suna & Kemer, 2022), whereby RSE resulted in learning engagement and RE (Eginli & Dikilitas, 2022;Hall, 2010;Heng et al, 2020;Jorgenen & Ducan, 2015;Salgueira et al, 2012;Pachler et al, 2019;Wu et al, 2020). RTE serves RI, a tendency for students to conduct research after graduation, including conducting research to develop the field, conducting research for career advancement, and conducting social research (Burke & Prieto, 2019;Livinƫi et al, 2021;Snelgrove & James, 2010).…”
Section: The Conceptual Model Developmentmentioning
confidence: 78%
“…Furthermore, previous proposals have suggested an association between the RTE and research self-efficacy (RSE) (Brown et al, 1996;Law & Gou, 2011;Livinƫi et al, 2021;Lynch et al, 2009). Moreover, RSE has been found to be associated with both RE (Eginli & Dikilitas, 2022;Hall, 2010;Heng et al, 2020;Jorgenen & Ducan, 2015;Salgueira et al, 2012;Pachler et al, 2019;Wu et al, 2020) and RI (Livinƫi et al, 2021;Pachler et al, 2019;Wu et al, 2020). Notably, all of these research studies were conducted in a non-educational context, for example psychology (Bruke et al, 2019), counselling (Jorgensen & Duncan, 2015), and medication (Black et al, 2013), employing a research framework that focused on examining each variable individually rather than collectively within a single study.…”
Section: Introductionmentioning
confidence: 96%